Mondhuk Entar Ngajhi Ben Ngabdhi - Arifin, Samsul; Fatah, Zaehol; Sari, Iin Puspita (Proceedings of Annual Conference for Muslim Scholars, 2024)
Pesantren are growing rapidly and are among the most popular choices for learning to improve Islamic values in the digital era in maintaining social harmony. However, there has been no research on the reasons for walisantri in making decisions to choose pesantren as a place of learning for their children. This study aims to explain the motivational needs survey of walisantri (parents of students) in determining the choice of Salafiyah Syafi'iyah Situbondo pesantren in the perspective of McClelland's theory. The research method used a survey approach with cluster sampling of 613 people. The survey results showed a high score for the need for achievement of 4.69 or strongly agree and the need for belonging of 4.66 or strongly agree. This is consistent with the pesantren's slogan, "Mondhuk entar ngajhi ben ngabdhi (mondok to learn and do service)," which can mean mondok to learn to deepen knowledge and maintain social harmony. McClelland's theory shows that walisantri's need for achievement and belonging significantly influences their decision to send their children to pesantren. This research provides valuable insights that can help pesantren and other educational institutions meet the needs of parents and students, and increase the effectiveness and relevance of pesantren education in maintaining social harmonization. The research also contributes to the literature on pesantren and motivation theory.